BAHASA SEBAGAI ALAT PEMBERDAYAAN SISWA AGAR MANDIRI DALAM LINGKUNGAN PESANTREN - Eka Putri Vania; Moh. Ahsan Shohifur Rizal; Kholik (An Natiq, 2024)
This research is an in-depth effort to explore the role of language as a tool for empowering Islamic boarding school students to achieve an optimal level of independence. In the context of Islamic boarding schools, language is not only interpreted as a medium of communication, but also as a crucial instrument in forming character and understanding religious values. By integrating learning methods that focus on understanding religion in the context of everyday life, the aim of this research is to provide new insights in developing student empowerment strategies. The importance of understanding religious values permeated through language is the main focus, and this research seeks to make a significant contribution by detailing effective strategies to achieve this goal. It is hoped that the findings of this research can become a basis for Islamic boarding schools in designing learning that not only prioritizes aspects of student independence, but also integrates religious values as a whole in the daily lives of Islamic boarding school students.